Cognitive functioning mediates the relationship between self-perceptions of aging and computer use behavior in late adulthood: Evidence from two longitudinal studies - Mariano, J. (2021)
Although information and communication technologies have become an integral part of contemporary societies, substantial proportions of the older population remain distant from these digital tools. This stresses the importance of identifying age-specific factors that facilitate or prevent technology adoption among older age groups. Despite being powerful determinants of behavior and health in late adulthood, little is known about the role of stereotypical perceptions about age and aging in the behavioral engagement with technological devices. Across two longitudinal studies, we examined the relationship between self-perceptions of aging and computer use behavior, as well as the mediating role of cognitive functioning. Study 1 was based on the 2010, 2014, and 2018 waves of the Health and Retirement Study (n = 3404). Study 2 was based on the 2014 and 2017 waves of the German Ageing Survey (n = 4871). Both studies revealed that more positive self-perceptions of aging were associated with more frequent computer use behavior. Moreover, this relationship was partially mediated by cognitive functioning. This suggests that perceptions about their aging experience can influence how individuals behave towards computer technology by impacting important predictors of use behavior. Interventions promoting positive self-perceptions of aging may thus contribute to the digital inclusion of middle-aged and older adults.